1996
DOI: 10.1007/bf00057592
|View full text |Cite
|
Sign up to set email alerts
|

Human phylogenetic relationships according to the D1S80 locus

Abstract: By analyzing the allelic frequencies at the D1S80 locus in 43 human populations, we show that the locus is polymorphic globally and that it can be used to discriminate between major racial groups and subpopulations through phylogenetic analysis. Although the use of informative multiple loci generally provides more accurate phylogenetic relationships, in instances where time and/or target DNA availability is limited, D1S80 could provide useful data to discriminate between human groups. Also, knowledge of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…This finding likely reflects the mosaic of people from var- Table 1. ious tribes and regions of continental Africa that were brought to the Bahamas during slave trade and post slave trade events. These include representatives of the Igbo/Ebo, Mandingo, Fulani, Hausa (Albury, 1975), Yoruba, Congo (Albury, 1975;Duncan et al, 1996), Akan (Wilkie, 1993), Kru, Ndongo, and Mbundu (Saunders, 1996) peoples, originating from West and Central Africa among others. In addition to the genetic influences observed in this study, many cultural traditions from West and Central Africa (e.g., music (Goombay, Junkanoo), dance (Ring play), story-telling, obeah (black and white magic), ''bush'' medicine, and even the communal practice of money management, the ''Asue'') have been integrated into Bahamian society and still remain an important part of Bahamian culture (Saunders, 1995).…”
Section: Discussion Genetic Signatures Of the Transatlantic Slave Tradementioning
confidence: 99%
See 1 more Smart Citation
“…This finding likely reflects the mosaic of people from var- Table 1. ious tribes and regions of continental Africa that were brought to the Bahamas during slave trade and post slave trade events. These include representatives of the Igbo/Ebo, Mandingo, Fulani, Hausa (Albury, 1975), Yoruba, Congo (Albury, 1975;Duncan et al, 1996), Akan (Wilkie, 1993), Kru, Ndongo, and Mbundu (Saunders, 1996) peoples, originating from West and Central Africa among others. In addition to the genetic influences observed in this study, many cultural traditions from West and Central Africa (e.g., music (Goombay, Junkanoo), dance (Ring play), story-telling, obeah (black and white magic), ''bush'' medicine, and even the communal practice of money management, the ''Asue'') have been integrated into Bahamian society and still remain an important part of Bahamian culture (Saunders, 1995).…”
Section: Discussion Genetic Signatures Of the Transatlantic Slave Tradementioning
confidence: 99%
“…These investigations, which are based exclusively on classical (Halberstein et al, 1981) and autosomal STR (Duncan et al, 1996;Budowle et al, 1999;Herrera et al, 2004;Simms et al, 2008Simms et al, , 2010Simms et al, , 2011 polymorphisms, reveal substantial gene flow from continental Africa and varying degrees of genetic input from European, East Asian and Native American ancestors. In this article, we explore, for the first time, the paternal genetic histories of six Bahamian islands and their relationships with previously published reference collections using highresolution Y-chromosome binary markers.…”
mentioning
confidence: 99%
“…Subsequently, Budowle et al suggested the possibility of using D1S80 to differentiate populations (Budowle et al, 1991(Budowle et al, , 1995. The first investigation of the variability of this locus on a global scale, namely, in 43 populations from different regions of the world, was published by Duncan et al in 1996(Duncan et al, 1996. Clear distinctions were noted between populations of different main human groups and high similarity was shown among populations of the same main human group.…”
Section: D1s80 Minisatellite Polymorphism In Human Population Researchmentioning
confidence: 99%
“…6A and 6B, respectively) as well as in the substantially high HD values (Supplementary Tables 7 and 8, respectively), is strikingly diverse, suggesting that the Bahamian archipelago has been influenced by a wide array of African source populations. This finding is not surprising given that the Africans settling in the Bahamas were members of various tribes, including, but not limited to, the Igbo/Ebo, Mandingo, Fulani, Hausa (Albury, 1975), Yoruba, Congo (Albury, 1975;Duncan et al 1996), Akan (Wilkie, 1993), Kru, Ndongo and Mbundu (Saunders, 1996) peoples, originating throughout West and Central Africa. It is important to note that many cultural influences derived from these groups (e.g., music (Goombay, Junkanoo), dance (Ring play), storytelling, obeah (black and white magic), 'bush' medicine and even the communal practice of money management, the 'Asue') still remain a part of Bahamian tradition (Saunders, 1995).…”
Section: Genetic Signatures Of the Transatlantic Slave Tradementioning
confidence: 94%